Factors Related to the Low Visiting of Babies to Integrated Healthcare Center - Liyani, Unmul; Hilda, Hilda; Ariefah Putri, Rosalin (Rifa'Institute, 2023)
Introduction: As a form of community participation in utilizing Integrated Healthcare Center, it can be seen from the coverage divided by the number of targets (D/S). Based on data from the Integrated Healthcare Center Karangan Public Health Centre, the community visits to the Integrated Healthcare Center in 2022 reached (65.2%). From the data It is seen that this achievement is very far from the national target of 85%. Objective: This study aims to find out the factors of the low visiting of babies to Integrated Healthcare Center in the work area of Karangan Public Health Centrein 2023. Method: The research method was observational analytic with a cross-sectional approach. The population in this study was 80 toddlers aged 12-59 months in the work area of Karangan Public Health Centre in 2023. Results and Discussion: It is hoped that Health Promotion about the benefits of Integrated Healthcare Center needs to be carried out so that respondents want to bring their children to routine activities every month at the Integrated Healthcare Centerand for further researchers to continue this research by looking at others factors related to the visit of the mother toddler to the Integrated Healthcare Center. Conclusion: It showed that occupation, education, knowledge factors do not affect the low toddler visit to Integrated Healthcare Center while family support and mother's attitude affect the low toddler visit to Integrated Healthcare Center.